Sacerdotisa da NOVACAP: a trajetória mágica de Tia Neiva e a modernização do centro-oeste - Pontes, Jonael Lima (2021)
This research aims to understand how the trajectory of Neiva Chaves Zelaya took place and the constitution of his doctrine of Vale do Amanhecer – VDA. The investigations conducted here are guided by the attempt to apprehend why the emergence of religions in the scenario of the construction of NOVACAP-Nova Capital, just as Brasilia was known in its construction. Such affect, propose that the agents that operate such religious practices received encouragement from the State as well as other religions that emerged within the same landscape. The corpus of this work consisted of the survey and analysis of several manuals of publications published by the VDA itself, visits to rituals (before the Covid-19 pandemic) in order to reconstruct the perception about the studied phenomenon. This research, therefore, has a qualitative character given its intention to explore the practices of the agents involved in this context and the meanings shared in each of the information, photographs and academic works related to the studied theme. I thus identify the construction of social representations around the idea of Religion. As a general hypothesis, the idea that the practices of VDA had an immense incentive from the State through the interdependence networks that Tia Neiva was inserted is presented.